2016
DOI: 10.1016/j.jpeds.2016.02.072
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Lactoferrin in Gastrointestinal and Immune Development and Function: A Preclinical Perspective

Abstract: The early postnatal period is a critical time for gastrointestinal (GI) and immune development. Neonates fed mother's milk have more rapid GI and immune development than fed-formula infants. In addition, clinical and epidemiologic data provide strong evidence that breastfeeding reduces the incidence and/or severity of infectious diseases. Lactoferrin is a 77 kDa, iron-binding glycoprotein that is present at high concentration in human milk compared with bovine milk and infant formula. It is a multifunctional p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
62
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 90 publications
(63 citation statements)
references
References 126 publications
(213 reference statements)
0
62
0
1
Order By: Relevance
“…Many of these minor proteins are post-translational modified proteins and have their own biological functions. [28][29][30] Although very low in quantity, they may provide significant beneficial activities for infant in immune system and cognitive functions. 28,31,32…”
Section: Resultsmentioning
confidence: 99%
“…Many of these minor proteins are post-translational modified proteins and have their own biological functions. [28][29][30] Although very low in quantity, they may provide significant beneficial activities for infant in immune system and cognitive functions. 28,31,32…”
Section: Resultsmentioning
confidence: 99%
“…ITLN1 is a high affinity Lf receptor (Kd = 10 -6 M) able to transduce several Lf-mediated functions, ranging from facilitation of intestinal iron absorption in infants to strengthening of the immune system [87][88][89][90]. A thorough screening of adult murine tissues revealed that INTL1 is expressed in the digestive tract (esophagus, stomach, small intestine, and large intestine), nervous system (cerebellum, hypothalamus, hippocampus, pituitary gland, ganglia, and spinal cord), reproductive system (testes and ovaries) and other organs, such as the pancreas, renal cortex, lung, heart, and liver [91], thus suggesting its pivotal role into the redistribution of circulating Lf into the body.…”
Section: Lactoferrin Bioavailability: Absorption and Body Deliverymentioning
confidence: 99%
“…Colostrum is the first milk produced and is characterized for containing over 250 potentially immunologically active proteins, including enzymes (lactoferrin, lysozyme, etc. ), hormones, immunoglobulins, cytokines, signaling molecules, soluble receptors and inflammatory mediators . The high content of bioactive proteins evidenced that colostrum's main role is immunological rather than nutritional .…”
Section: Human Milk Among the Stages Of Lactationmentioning
confidence: 99%